1992
DOI: 10.1073/pnas.89.9.3937
|View full text |Cite
|
Sign up to set email alerts
|

Activation of EVI1 gene expression in human acute myelogenous leukemias by translocations spanning 300-400 kilobases on chromosome band 3q26.

Abstract: Retroviral activation ofEvi-l gene expression is one of the most common transforming events in murine myeloid leukemias. To evaluate the role of the EVII gene in human acute myelogenous leukemia (AML), leukemic blasts or cell lines from 116 patients were examined. In eight patients the EVII gene was expressed and all but one had cytogenetically detectable translocations of chromosome 3q26 where the EVII gene has been localized. To identify breakpoints, a restriction map that spans 1700 kilobases (kb) of the EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
222
0
1

Year Published

1996
1996
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(225 citation statements)
references
References 26 publications
1
222
0
1
Order By: Relevance
“…So far, by using pulsed field gel electrophoresis (PFGE) and fluorescence in situ hybridization (FISH) analyses, the breakpoints of the 3;3 translocations have been mapped 5Ј of EVI1, whereas the breakpoints of the inv(3) have been mapped 3Ј of the gene (Figure 2). 37,38 This defined orientation of the two breakpoints on chromosome 3 suggested that the activation could occur through inappropriate juxtaposition of EVI1 to the regulatory sequence of a gene located at 3q21. After cloning and molecular analysis of breakpoint junctions of the t(3;3) and inv(3), it was determined that both these rearrangements juxtapose the enhancer of the constitutively expressed housekeeping gene Ribophorin I to the coding region of EVI1.…”
Section: Involvement Of Evi1 In Myeloid Leukemiasmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, by using pulsed field gel electrophoresis (PFGE) and fluorescence in situ hybridization (FISH) analyses, the breakpoints of the 3;3 translocations have been mapped 5Ј of EVI1, whereas the breakpoints of the inv(3) have been mapped 3Ј of the gene (Figure 2). 37,38 This defined orientation of the two breakpoints on chromosome 3 suggested that the activation could occur through inappropriate juxtaposition of EVI1 to the regulatory sequence of a gene located at 3q21. After cloning and molecular analysis of breakpoint junctions of the t(3;3) and inv(3), it was determined that both these rearrangements juxtapose the enhancer of the constitutively expressed housekeeping gene Ribophorin I to the coding region of EVI1.…”
Section: Involvement Of Evi1 In Myeloid Leukemiasmentioning
confidence: 99%
“…38 The breakpoints of the t(3;3) are not localized to a restricted region upstream of EVI1, but occur over a genomic region of 13-300 kb 5Ј of the gene, and lead to full activation of the gene by juxtaposition of the Ribophorin I enhancer. 37,38 Although inappropriate activation of genes caused by chromosomal rearrangements over such a large distance are not very common, they have been reported before.…”
Section: Involvement Of Evi1 In Myeloid Leukemiasmentioning
confidence: 99%
“…Primary murine (Bergeron et al, 1992) and human leukaemia cells (Morishita et al, 1992a) also have retroviral insertions or translocations, respectively, which activate Evi-1 gene expression. Several lines of evidence strongly suggest that the activation of Evi-1 expression contributes to cell transformation: (1) Some translocations produce either a truncated (Ogawa et al, 1996;Suzukawa et al, 1997) or a fusion Evi-1 protein product (Mitani et al, 1994); (2) Evi-1 is overexpressed in ovarian cancers (Brooks et al, 1996) suggesting a link with other cancers as well as leukaemia; (3) Constitutive Evi-1 expression in both primary erythroid progenitor cells and 32Dcl3 myeloid cells (Morishita et al, 1992b) results in the loss of erythropoietin responsiveness and G-CSF-dependent survival respectively; and (4) Evi-1 transforms Rat1 ®broblasts (Kurokawa et al, 1995).…”
mentioning
confidence: 99%
“…The abnormal expression of the EVI-1 gene has been assonarrowed the breakpoint region to the interval between YACs 929a11 and 807g5, bands 3q21-22 (Figure 1). ciated with blast crisis of CML, AMLs and myelodysplastic syndromes [25][26][27][28] and we showed that EVI-1 is maintained on Finally the karyotype of the leukemic cells from our JMML patient was revised as 46,XX,der(12)t(3;12)(q21 ෂ 22;p13.33).…”
mentioning
confidence: 87%